2022
DOI: 10.3390/w14030401
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Fate of Rare Earth Elements, REE, in Transitional Environments: Coasts and Estuaries

Abstract: The production of rare earth elements, REE, has significantly increased over the past years, in parallel with the latest advances in nanotechnologies and representing a new group of emerging contaminants. They find application in construction, transport, agriculture, electronics, catalysis, and biomedicine. Their extraordinary intrinsic characteristics are fundamental for overcoming current technological challenges. The accumulation of REE is consistent in near-shore waters being affected by runoff, wastewater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 217 publications
0
7
0
Order By: Relevance
“…The natural REE concentrations in seawater are usually very low (10 −6 – 10 −9 g/L), increasing several order of magnitude in sites impacted by anthropogenic sources such as the discharge of industrial wastewater and e-waste leachates (Arienzo et al 2022 ). For example, values of 130–152 μg REEs/L were reported in surface waters in areas affected by mining activities (Liang et al 2014 ), which are in line with the range of concentrations of the present study, highlighting the potential of the approach to remediate contaminated environments.…”
Section: Resultsmentioning
confidence: 99%
“…The natural REE concentrations in seawater are usually very low (10 −6 – 10 −9 g/L), increasing several order of magnitude in sites impacted by anthropogenic sources such as the discharge of industrial wastewater and e-waste leachates (Arienzo et al 2022 ). For example, values of 130–152 μg REEs/L were reported in surface waters in areas affected by mining activities (Liang et al 2014 ), which are in line with the range of concentrations of the present study, highlighting the potential of the approach to remediate contaminated environments.…”
Section: Resultsmentioning
confidence: 99%
“…The transition from traditional to greener energy sources (e.g., wind turbines) and countless high-tech devices rely on rare-earth elements (REE), whose mining and processing are environmentally unfriendly [1]. Increasing REE concentrations in water bodies due to ineffective treatment in wastewater treatment plants and leaching from untreated e-waste have been reported worldwide [2]. Recent studies have shown that REE have toxic effects on aquatic organisms, underscoring the importance of removing these emerging contaminants from water [3].…”
Section: Extended Abstractmentioning
confidence: 99%
“…Of these, Ce, La and Nd are the most abundant REE on the planet (Wall 2014). Moreoevr, REE are categorized as critical resource materials of modern industry, and so are extremely important constituents for high technology industrial applications (Arienzo et al 2022). However, REE toxicity with regard to commercial plant species in terms of growth reduction, chlorosis, photosynthesis disruption, and eventually plant death, has been reported (Zhang et al 2023).…”
Section: Heavy Metals (Hm) and Rare Earth Elements (Ree)mentioning
confidence: 99%